Antioxidant enzyme activity and growth responses of Huangguogan citrus cultivar to nitrogen supplementation. Issue 10 (3rd October 2019) - Liao, Ling; Dong, Tiantian; Qiu, Xia; Rong, Yi; Sun, Guochao; Wang, Zhihui; Zhu, Jin
ABSTRACT: This study examined the physiological effects of different amounts of nitrogen (N) supplementation (0 to 2.72 kg/year) on the citrus cultivar Huangguogan ( Citrus reticulata × Citrus sinensis ). Root activity, chlorophyll content, and fruit quality were measured, and the activities of the antioxidant enzymes superoxide dismutase (SOD), guaiacol peroxidase (POD), and catalase (CAT), and the contents of malondialdehyde (MDA) and soluble protein in root, leaf, and fruit tissues were examined at different developmental stages. Root activity, chlorophyll content, fruit quality, antioxidant enzyme activity, MDA content, and soluble protein content increased in plants treated with an appropriate amount of N. Both excessive N and N deficiency decreased the content of MDA and the activities of antioxidant enzymes. Application of 1.36–1.81 kg N/year is suggested for citrus fertilization and the lower end of this range is recommended for minimizing environmental impact and production cost. Graphical abstract: : Root activity, chlorophyll content, fruit quality, SOD, POD, CAT, MD, and soluble protein increased in plants treated with an appropriate amount of N, but limited with excessive N.